2011
DOI: 10.1007/s12192-011-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjuvant activity of N- and C-terminal domain of gp96 in a Her2-positive breast cancer model

Abstract: It has been frequently reported that gp96 acts as a strong biologic adjuvant. Some studies have even investigated adjuvant activity of the gp96 C-or N-terminal domain. The controversy surrounding adjuvant activity of gp96 terminal domains prompted us to compare adjuvant activity of gp96 C-or N-terminal domain toward Her2/neu, as DNA vaccine in a Her2/neu-positive breast cancer model. To do so, mice were immunized with DNA vaccine consisting of transmembrane and extracellular domain (TM + ECD) of rat Her2/neu a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Taken together, these studies demonstrate that the use of GRP94 as an antitumor vaccination can prevent cancer development. However, GRP94 vaccination in mice appears less promising in the treatment of established tumors 114,116,117 , and clinical trials across various types of tumors suggest that autologous tumor-derived GRP94 vaccination may have limited efficacy 118121 .…”
Section: The Role Of Grp94 and Other Chaperones In Antitumor Vaccinationmentioning
confidence: 99%
“…Taken together, these studies demonstrate that the use of GRP94 as an antitumor vaccination can prevent cancer development. However, GRP94 vaccination in mice appears less promising in the treatment of established tumors 114,116,117 , and clinical trials across various types of tumors suggest that autologous tumor-derived GRP94 vaccination may have limited efficacy 118121 .…”
Section: The Role Of Grp94 and Other Chaperones In Antitumor Vaccinationmentioning
confidence: 99%
“…According to the obtained results, immune-stimulatory properties of different gp96 domains may be affected by the antigen of interest. 49 Even, the reports on the adjuvant activity of C-terminal domain of gp96 are controversial, depending on the antigen. 50,51 The data showed that the construct containing the C-terminal of gp96 fused with Her2/neu, but not the co-administration of the two separated constructs, decreased CD4+CD25+foxp3+ regulatory T cells at the tumor site and enhanced CTL activity as well as IFN-γ secretion.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%